2020
DOI: 10.21203/rs.3.rs-112941/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corneal Nerve Fiber Loss Relates to Cognitive Impairment in Patients with Parkinson’s Disease

Abstract: Background Cognitive impairment in Parkinson’s disease (PD) adversely influences quality of life. There is currently no available biomarker to predict cognitive decline in PD. PD involves both the central and peripheral nervous system and especially small fiber damage occurs in PD. Corneal confocal microscopy (CCM) has been used as a non-invasive tool for quantifying small nerve fibre damage in PD. The present study investigated whether corneal nerve measures were associated with cognitive function in PD. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…69 In a recent study from China, CNFD showed excellent diagnostic performance for CCM, with an AUC of 0.96 for PD and corneal nerve fiber parameters correlated with the severity of motor symptoms measured using the H-Y stage, UPDRS-III, and UPDRS-total. 70 Furthermore, we have shown that a lower CNFL predicts progressive worsening of UPDRS-III over 12 months in patients with PD. 71 CCM could therefore complement the diagnostic toolbox for pre-motor Parkinson's disease.…”
Section: Ccm In Central Neurodegenerative Diseasementioning
confidence: 87%
“…69 In a recent study from China, CNFD showed excellent diagnostic performance for CCM, with an AUC of 0.96 for PD and corneal nerve fiber parameters correlated with the severity of motor symptoms measured using the H-Y stage, UPDRS-III, and UPDRS-total. 70 Furthermore, we have shown that a lower CNFL predicts progressive worsening of UPDRS-III over 12 months in patients with PD. 71 CCM could therefore complement the diagnostic toolbox for pre-motor Parkinson's disease.…”
Section: Ccm In Central Neurodegenerative Diseasementioning
confidence: 87%